Effect of irrigation on the growth and yield of (Daucus carota ssp. sativus) carrot in hill valley - Alam, MS; Mallik, SA; Costa, DJ; Alam, MS; Alam, A (Bangladesh Journal of Agricultural Research, 2010)
Experiments were conducted at Hill Agricultural Research Station, Khagrachari during the period from November to February in 2005-06 and 2006-07 to determine the appropriate irrigation schedule for carrot production in hill valley. The experiment consisted of five treatments of irrigation after plant established viz. No irrigation (I0), irrigation at 1W: CPE of 0.6 (I1), irrigation at 1W: CPE of 0.8 (12), irrigation at 1W: CPE of 1.0 (I3) and irrigation at 1W: CPE of 1.2 (I4). The amount of irrigation water (IW) was fixed at 4 cm. The experiment was laid out in RCBD with 3 replications. The treatments significantly influenced the growth, yield contributing characters and yield of carrot. Among the treatments, irrigation at IW: CPE of 1.2 gave the maximum yield (51.47 t/ha) which received 4 irrigations after plant stand with applied total irrigation water of 16 cm resulting in the highest net return of Tk. 120,443 with the highest BCR of 2.41. It also produced carrot at the lowest production cost of Tk. 1.66 per kg. Irrigation water use efficiency was obtained 1705.63 kg/ha/cm by this treatment. Keywords: Irrigation; growth; yield; carrot. DOI: 10.3329/bjar.v35i2.5895 Bangladesh J. Agril. Res. 35(2) : 323-329, June 2010